Sandviç Kumaşın Çeşitli Basma Yüklemeleri Altında Modellenmesi - (:unkn) unknown (My University, 2018)
Sandviç kumaş tekstil endüstrisinden geleneksel kumaşlara göre avantajlı özellikleri sayesinde kayda değer ilgi görmektedir. Sandviç kumaşçoklu iplik katmanlarının tekli iplikler ile bağlanması sonucu oluşmuştur, ve bu hava geçirgenliği yüksek sandviç yapıyı oluşturur.Buna binaen iyi termal ve nem kontrolü sağlanır. Ayrıca deri konforu da ara yüzdeki temas basıncının düzgün dağılması ile gelişmektedir.Kontak yüzeydeki yük dağılımını ve basma kuvvetine karşı sandviç kumaş davranışını anlamak önemlidir. Bu çalışma ilk olarak detaylı birimhücrenin sonlu eleman analizi (SEA) modelini açıklamaktadır. Sonrasında model sonuçlarını deney sonuçları ile kıyaslamaktadır. Bunaek olarak hiperelastik ampirik SEA modelleme yöntemi sunulmuştur, bu yöntem sayesinde tasarımcılar sandviç kumaş performansını tasarım aşamasında değerlendirebileceklerdir.

Spacer fabric attracts considerable attention from textile industry due to its advantageous properties compared to conventional fabrics. It has two outer layer that is formed with multifilaments (knitted substrates), and spacer yarns (monofilaments) connect between the substrates. Therefore, it provides good thermal and humidity control. Shoes, backpacks, car seat cushions, bras and mattresses are started to get benefits of spacer fabrics to manage heat and vapor better. Also, spacer fabric is an example of a sandwich structure that provides high mechanical strength at a low specific weight. Moreover, comfort of the skin improves by distributing the contact pressure at the interface. Understanding the stress distribution at the contact and response to the compressive loading is important for the spacer fabric. This study first describes the FEA modeling of the spacer fabric in detailed unit cell. Each fiber interaction in the unit cell was included in the models. Then, the model results were compared to the experiments. The detailed model showed the fiber behavior during the compression. Besides that, hyperelastic empirical FEA model methodology was presented. With this approach, hyperelastic material properties were defined to mimic the spacer fabric reaction to the loading. By homogenizing the solid body of the spacer fabric, simulation times reduced significantly. Uniformization method is expected to allow the designers to test the spacer fabric performances in designing phase.
Modeling of a Spacer Fabric Under Various Compressive Loads
Keywords: Malzeme Bilimleri, Tekstil